Foraging behaviour and dry matter intake by lambs in a silvopastoral system: Foraging and Intake in silvopastoral systems - López-Ortiz, Silvia; Valenzuela-Gonzalez, Viviana; Pérez-Ramírez, Efrain; Vargas-Mendoza, Mónica de la Cruz; Jarillo-Rodríguez, Jesús; Salazar-Ortiz, Juan; Díaz-Rivera, Pablo (Ecosistemas y Recursos Agropecuarios, 2021)
Dry matter intake, nutritional contribution of forage to the diet and Lamb foraging behavior were assessed in a silvopastoral system. Twelve Pelibuey female lambs (6.3 months of age, 23.74 ± 3.5 kg live weight), were randomly assigned to two treatments: pastures of Digitaria eriantha (monoculture) or pastures of D. eriantha and Guazuma ulmifolia (silvopastoral). During a 15 day period, lambs foraged individually in 20.14 m2 paddocks each day; time spent grazing and browsing were assessed by scan sampling; dry matter intake was estimated (day 11-15), using the chromic oxide (Cr2O3) method, and metabolizable energy (ME) and protein (CP) ingested by the lambs were estimated. Data analyses were performed using a complete randomized design (dry matter intake) and a repeated-measure design (ME and CP, foraging time) with factorial treatment structure of season (windy and dry) and pasture (monoculture and silvopastoral). Voluntary intake (season*treatment interaction, p = 0.015) was lower in the windy-silvopastoral treatment (448.5±38.2 g day-1) than in the other treatments (625.8±38.2 to 680.5±38.2 g day-1). The contribution of ME (719.7-1190.2 kcal·day-1) and CP (53.7-100.7 g day-1) was low to cover the lamb requirements in all treatments, because forage availability and dry matter intake were low. Lambs dedicated from 6.65±0.26 to 7.50 ± 0.26 h to foraging; time spent grazing was longer that browsing in the silvopastoral system (p < 0.0001). The time dedicated to foraging, intake, and nutritive quality of forage from in both pasture types did not provide nutrients and energy during any season for maintenance of the lambs.